Do mental health consumers want to improve their long‐term disease risk behaviours? A survey of over 2000 psychiatric inpatients. (2nd December 2017) - Bartlem, Kate; Bailey, Jacqueline; Metse, Alexandra; Asara, Ashley; Wye, Paula; Clancy, Richard; Wiggers, John; Bowman, Jenny
Abstract: Policies and clinical guidelines acknowledge the role mental health services have in addressing the physical health of individuals with a mental illness; however, little research has explored interest in reducing health risk behaviours or the acceptability of receiving support to reduce such risks among psychiatric inpatients. This study estimated the prevalence of four long‐term disease risk behaviours (tobacco smoking, hazardous alcohol consumption, inadequate fruit and/or vegetable consumption, and inadequate physical activity); patient interest in reducing these risks; and acceptability of being provided care to do so during a psychiatric inpatient stay. A cross‐sectional survey was undertaken with 2075 inpatients from four inpatient psychiatric facilities in one health district in Australia (October 2012–April 2014). Prevalence of risk behaviours ranged from 50.2% (inadequate physical activity) to 94.8% (inadequate fruit and/or vegetable consumption). The majority of respondents (88.4%) had more than one risk behaviour, and most were seriously considering improving their risk behaviours (47.6% to 65.3%). The majority (80.4%) agreed that it would be acceptable to be provided support and advice to change such behaviours during their psychiatric inpatient stay. Some diagnoses were associated with smoking and hazardous alcohol consumption, interest in reducing alcohol consumption and increasing fruit and/or vegetable consumption, and acceptability of receiving advice and support. The findings reinforce the need and opportunity for psychiatric inpatient facilities to address the long‐term disease risk behaviours of their patients.